Adherence to Barcelona Clinic Liver Cancer therapeutic algorithm for hepatocellular carcinoma in the daily practice: a multicenter cohort study from Argentina. Issue 4 (April 2018) - Piñero, Federico; Marciano, Sebastián; Fernández, Nora; Silva, Jorge; Zambelo, Yanina; Cobos, Manuel; Zerega, Alina; Ridruejo, Ezequiel; Miguez, Carlos; Ameigeiras, Beatriz; D'Amico, Claudia; Gaite, Luis; et al.
Abstract : Background and aim: Adherence to the Barcelona Clinic Liver Cancer (BCLC) staging algorithm for the treatment of hepatocellular carcinoma is challenging in the daily practice. We aimed to analyze adherence to BCLC along with its effect on patient survival. Patients and methods: A cohort study was conducted in 14 hospitals from Argentina including patients with newly diagnosed hepatocellular carcinoma (2009–2016). Adherence was considered when the first treatment was the one recommended by the BCLC. Results: Overall, 708 patients were included. At diagnosis, BCLC stages were as follows: stage 0 4%, A 43%, B 22%, C 9% and D 22%. Overall, 53% of the patients were treated according to BCLC, 24% were undertreated, and 23% overtreated. Adherence to BCLC increased to 63% in subsequent treatments. Independent factors associated with adherence to BCLC were the presence of portal hypertension [odds ratio: 1.63; 95% confidence interval (CI): 1.11–2.39] and BCLC stage C (odds ratio: 0.32; 95% CI: 0.12–0.72). In a multivariable model adjusting for portal hypertension and BCLC stages, adherence to BCLC showed improved survival (hazard ratio: 0.67; 95% CI: 0.52–0.87). Conclusion: Adherence to BCLC represents a challenge in the daily practice, with almost half of the patients being treated accordingly, showing that the decision-making process should be tailored to each individual patient. Abstract : Supplemental Digital Content is available in the text.